2022
DOI: 10.1101/2022.05.22.492882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A global atlas of substrate specificities for the human serine/threonine kinome

Abstract: Protein phosphorylation is one of the most widespread post-translational modifications in biology. With the advent of mass spectrometry-based phosphoproteomics, more than 200,000 sites of serine and threonine phosphorylation have been reported, of which several thousand have been associated with human diseases and biological processes. For the vast majority of phosphorylation events, it is not yet known which of the more than 300 protein Ser/Thr kinases encoded in the human genome is responsible. Here, we util… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 108 publications
(124 reference statements)
1
28
0
Order By: Relevance
“…If so, this would be a potentially powerful tool for the identification of native substrates and the dissection of phosphotyrosine signaling pathways. Indeed, oriented peptide libraries have been applied extensively to predict the native substrates of protein kinases (Johnson et al, 2022; Miller et al, 2008; Obenauer et al, 2003). We are particularly interested in using high-throughput specificity screens to predict how mutations proximal to phosphorylation sites affect tyrosine kinase selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If so, this would be a potentially powerful tool for the identification of native substrates and the dissection of phosphotyrosine signaling pathways. Indeed, oriented peptide libraries have been applied extensively to predict the native substrates of protein kinases (Johnson et al, 2022; Miller et al, 2008; Obenauer et al, 2003). We are particularly interested in using high-throughput specificity screens to predict how mutations proximal to phosphorylation sites affect tyrosine kinase selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The specificity profiling screens described thus far were constrained to sequences that contain the canonical twenty amino acids. Several studies have suggested that non-canonical amino acids and post-translationally modified amino acids can also impact sequence recognition by tyrosine kinases and SH2 domains (Alfaro-Lopez et al, 1998; Begley et al, 2015; Chapelat et al, 2012; Johnson et al, 2022; Yeh et al, 2001). The most notable example of this is phospho-priming, whereby phosphorylation of one residue on a protein enhances the ability of a kinase to recognize and phosphorylate a proximal residue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This corroborates the value of introducing a sequence similarity-based feature in network inference strategies and highlights the importance of reducing the noise in a dataset before applying network inference methods. In addition, efforts have recently been made to identify the substrate recognition motifs for all kinases 43,44 , which will further improve our ability to reduce noise and match kinases to the correct substrates. Additional ways to reduce noise in the dataset could include filters to include phosphosites that are predicted to be functional 45 , and introducing very strict p-value and fold-change cut-offs for the identification of differentially abundant phosphosites.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous mechanisms can underlie signaling specificity by protein kinases, including subcellular compartmentalization, scaffolding, signal dynamics, and direct kinase-substrate interactions 6 . One mechanism common to Ser/Thr protein kinases involves the recognition of sequence motifs surrounding sites of phosphorylation by the catalytic cleft 7 . However, since all MAPKs target a common Ser/Thr-Pro consensus sequence, catalytic site specificity is insufficient to mediate selectivity for a particular member of the family.…”
Section: Introductionmentioning
confidence: 99%